PENGARUH MEDIA PEMBELAJARAN POWERPOINT MELALUI METODE DISCOVERY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MAHASISWA - Rahma Hidayati Darwis (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
This type of research is a pseudo-exprimen that aims to know the influence of the application of powerpoint learning media through guided discovery methods to student problem solving skills. It says pseudo-excrement because not all variables that can affect a student's problem solving skills can be controlled. Variables that are manipulated are only free variables that are learning by using powerpoint learning media through discovery methods and the bound variable is the problem solving ability of students of Inferential Statistics Courses. Through the analysis stage obtained a conclusion that the use of powerpoint media through the approach of learning discovery makes students more active in the learning process so as to provide stimulation to the thinking ability of students. In addition, through the activities carried out such as making observations and comparisons with several problems relevant to the material, obtaining guidance in making patterns as embryos of the meaning of concepts, being actively involved in discussions, there were significant positive changes to the problem-solving abilities of participants. Educate